A moving blocks empirical likelihood method for longitudinal data. Issue 3 (11th May 2015) - Qiu, Jin; Wu, Lang
Summary: In the analysis of longitudinal or panel data, neglecting the serial correlations among the repeated measurements within subjects may lead to inefficient inference. In particular, when the number of repeated measurements is large, it may be desirable to model the serial correlations more generally. An appealing approach is to accommodate the serial correlations nonparametrically. In this article, we propose a moving blocks empirical likelihood method for general estimating equations. Asymptotic results are derived under sequential limits. Simulation studies are conducted to investigate the finite sample performances of the proposed methods and compare them with the elementwise and subject‐wise empirical likelihood methods of Wang et al. (2010, Biometrika 97, 79–93) and the block empirical likelihood method of You et al. (2006, Can. J. Statist . 34, 79–96). An application to an AIDS longitudinal study is presented.